Palm Stick Plates: Efforts to Improve the Economy Children's Tribe in Jambi - Kurniasih Setyagustina Setyagustina; Muhammad Nuzli; Ainul Mardhiah; Muthiah Primadya (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
The SAD settlement in Pulau Tujuh Village is in the middle of an oil palm plantation. The village of Pulau Tujuh is the source of life for SAD at this time. Almost all the SAD there earn their livelihood by collecting rice palm fruit left over from the palm oil harvest because that is their only skill. Based on the survey, it was found that there are several problems, namely: The Trans Social SAD community in Pulau Tujuh Village currently only focuses on collecting palm oil palm kernels so their income is very low. There has not been optimal utilization of the potential resources in their environment, such as palm oil waste which is managed by the SAD community to become a product with economic value and high artistic value. There has been no transfer of science and technology to the SAD community to utilize the natural potential resources around them. utilizing the potential of palm oil stick waste to become handicrafts that have economic value for the welfare of the SAD community as well as a way to market the products they produce. PkM Activities 1) Increasing the knowledge of the SAD Pulau Tujuh Village community, regarding managing the potential resources they have to improve their economy, 2) Increasing the knowledge of the SAD Pulau Tujuh community about the benefits of palm oil waste into economically valuable products, 3) Providing assistance and training to the SAD community of Pulau Tujuh village how to make piling from palm oil stick waste into a handicraft, determine the cost of production and how to market it. This service activity is provided in the form of training. The methods used are: lectures, questions and answers, sharing ideas, practice/exercises on how to implement and maintain the system.